STRATEGI HUMAS PT SUNTORY GARUDA BEVERAGES DALAM KEGIATAN CSR MIZUIKU - Muminto Arief; Ratih Khairunnisa (Jurnal Pustaka Komunikasi, 2020)
The background of this research is based on seeing the current condition of clean water in Indonesia is scarce, and seeing how in Indonesia there is still very little knowledge about clean water management and how important it is to preserve clean water. As the basis of this research, we use the theory of 4 steps of effective communication strategies Public Relations and Kotler and Lee The Concept of CSR . The research of this paper uses a qualitative approach with a case study method. The purpose of this study was to find out the implementation of the Mizuiku Corporate Social Responsibility Strategy Program (Education Class I Love Clean Water) PT. Suntory Garuda Beverages, besides knowing the obstacles faced during the implementation of the Mizuiku Corporate Social Responsibility Strategy Program (Education Class I Love Clean Water) PT. Suntory Garuda Beverages. The results of this research show the strategies used by Public Relations of PT Suntory Garuda Beverages in the Mizuiku CSR program (Education Class I Love Clean Water) which is present as a real work from Suntory to take an active role in campaigning for environmental concerns, especially clean water in Indonesia.